Increasing Knowledge, Attitude, and Practice in using Traditional Medicines through Pharmacist’s Education and Mentoring in Mojokerto - Andito, Didik; Wijayanti, Tri; Herdwiani, Wiwin (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: The use of traditional medicines globally continues to increase and must be balanced with increased knowledge, attitudes, and practice in using traditional medicines through pharmacist education and mentoring.Objectives: This research aims to determine the description of the use of traditional medicine, the level of knowledge, attitudes, and practice of the community in using it, and the influence of pharmacist education and mentoring on it.Methods: This research design was quasi-experimental with a pre-test and post-test control group with 406 community research subjects. It involved 14 pharmacists in providing education and mentoring through WhatsApp group media by providing material according to the modules prepared. The instrument used a questionnaire developed from previous research and tested for validity and reliability. Data collection was carried out prospectively by the participant-self, and analyzed using the Wilcoxon Signed Ranks Test.Results: This study's total number of respondents was 406, divided into 203 as the intervention group and 203 as the control group. The description of the respondent's KAP level before the intervention is in the medium category and after the intervention is in the high category based on the Wilcoxon Signed Ranks Test results at a 95% confidence level (α=0.05) in the intervention group.Conclusion: The use of traditional medicines in the phytopharmaca class is 3%, standardized herbal medicines are 35%, and jamu is 62%. The level of knowledge, attitudes, and practice of the community in using traditional medicine in Mojokerto Regency is, on average, in the medium category. This research also shows the influence of pharmacist education and mentoring on increasing knowledge, attitudes, and practice scores from medium to high.